SUPERVISI AKADEMIK PENGAWAS SEKOLAH UNTUK MENINGKATKAN PROFESIONALISME GURU - Susilo; Fauzin Futiarso; Hardi Jatmiko; Su'ad; Ahmad Hariyadi (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2023)
The purpose of this research is to describe the academic supervision of school supervisors to improve teacher professionalism, which focuses on: (1) the implementation of academic supervision by school supervisors, (2) obstacles to academic supervision carried out by school supervisors, and (3) the efforts given by school supervisors under academic supervision. The research method used is a qualitative approach. Data collection procedures using interview techniques, observation, and documentation. Data analysis was carried out with the stages of data reduction, data display, and conclusion. The validity of the data using source triangulation techniques, technical triangulation; and time triangulation. The results showed that academic supervision carried out by school supervisors had been carried out properly and by following per under with applicable regulations, from planning to reporting the results of academic supervision; Although in its implementation there are still various obstacles, the effect is not so significant on the effectiveness of the implementation of academic supervision.